Black Cumin (Nigella sativa) Immunopotentiates Humoral Response in Commercial Broiler Chickens (African Journal of Biomedical Research, 2023)
Nigella sativa (Black cumin) is a widely used medicinal plant for the treatment of various diseases and ailments in humans and animals, but its use in poultry husbandry is limited. This study investigated the clinicopathological and humoral immune responses of commercial broiler chickens administered with Nigella sativa extracts and also vaccinated against Newcastle disease virus (NDV). There were five experimental groups A-E; A-were administered with Nigella sativa only (6). B- were vaccinated with Newcastle disease vaccine and administered with low dose of Nigella sativa L (6), C- were vaccinated with Newcastle disease vaccine and administered with high dose of Nigella sativa L, (6). D- those that were vaccinated with Newcastle disease vaccine only (6). E- negative control (6). The birds were monitored for weight changes, while blood and sera samples were collected for haematological and serological analysis following standard procedures. Birds administered with Nigella sativa only (A) and those vaccinated alone (D) and those with NDV-Nigella sativa combination (B, C) have higher weight gains compared to negative control (group E). Those vaccinated with NDV only (D) had higher antibody titre against ND virus at weeks 1, 2, and 3, compared to those birds vaccinated with low Nigella sativa, while in the 4th and 5th week, Groups with NDV vaccine-Nigella sativa combination (B&C) expressed a more significantly higher titre values. Group C birds vaccinated and administered with high dose of Nigella sativa had the highest antibody titre against ND virus throughout the weeks of experiment until week 5 when Group A (Nigella sativa only) showed a much higher NDV titre compared to other groups. In conclusion, administration of Nigella sativa improved body weight of chickens through feed conversion and also causes a more enhanced antibody response to NDV.